MHC-II presentation by oral Langerhans cells impacts intraepithelial Tc17 abundance and Candida albicans oral infection via CD4 T cells - Bittner-Eddy, Peter D.; Fischer, Lori A.; Parachuru, Praveen Venkata; Costalonga, Massimo (Frontiers in Oral Health, 2024)
In a murine model (LCΔMHC-II) designed to abolish MHC-II expression in Langerhans cells (LCs), ∼18% of oral LCs retain MHC-II, yet oral mucosal CD4 T cells numbers are unaffected. In LCΔMHC-II mice, we now show that oral intraepithelial conventional CD8αβ T cell numbers expand 30-fold. Antibody-mediated ablation of CD4 T cells in wild-type mice also resulted in CD8αβ T cell expansion in the oral mucosa. Therefore, we hypothesize that MHC class II molecules uniquely expressed on Langerhans cells mediate the suppression of intraepithelial resident-memory CD8 T cell numbers via a CD4 T cell-dependent mechanism. The expanded oral CD8 T cells co-expressed CD69 and CD103 and the majority produced IL-17A [CD8 T cytotoxic (Tc)17 cells] with a minority expressing IFN-γ (Tc1 cells). These oral CD8 T cells showed broad T cell receptor Vβ gene usage indicating responsiveness to diverse oral antigens. Generally supporting Tc17 cells, transforming growth factor-β1 (TGF-β1) increased 4-fold in the oral mucosa. Surprisingly, blocking TGF-β1 signaling with the TGF-R1 kinase inhibitor, LY364947, did not reduce Tc17 or Tc1 numbers. Nonetheless, LY364947 increased γδ T cell numbers and decreased CD49a expression on Tc1 cells. Although IL-17A-expressing γδ T cells were reduced by 30%, LCΔMHC-II mice displayed greater resistance to Candida albicans in early stages of oral infection. These findings suggest that modulating MHC-II expression in oral LC may be an effective strategy against fungal infections at mucosal surfaces counteracted by IL-17A-dependent mechanisms.